Situacion actual de la ganaderia de carne en el Ecuador - Ortiz Alarcon, Fausto (Revista Universidad de Guayaquil, 1983)
The tradition that Ecuador has been and is an essentially agricultural country has been devoured by the oil fever due to the lack of a coherent agricultural policy, among other evils that the Ecuadorian agricultural sector has endured; I have lost my sense, my serenity and instead of thinking sanely, taking advantage of the fleeting and transitory money from oil, investing it in permanent companies such as agriculture and livestock that, in addition to giving us strength for commerce and industry, gave us the basics, the first the food; especially now that the world is inevitably entering the stage of scarcity and famine that frighteningly alarms both rich and poor people, large and small.